A Taqriz for a Nineteenth Century Indonesian Manuscript - Kaptein, Nico J.G. (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
In medieval Arabic literature, a taqrīẓ is a written endorsement of a certain text, provided by a prestigious scholar at the request of another scholar to support the latter’s new writing. In this sense, it can be likened to the contemporary "blurb," serving to advertise a new book. The taqrīẓ holds significance as it facilitates connections and provides insights into active networks of like-minded scholars. However, this topic remains insufficiently explored, and the present paper seeks to contribute to its understanding. The research delves into an original taqrīẓ from the nineteenth century, obtained by a scholar in Batavia from his former teacher in Mecca. The paper reveals that the tradition of taqrīẓ persists into more modern times and extends beyond the Arab world.